Legally Aware Environmental Waste Management Efforts in the Puri Zahara 2 Housing Complex, Medan Selayang Subdistrict - Mahmud Mulyadi; Mahmul Siregar; Rosmalinda; Vita Cita Emia Tarigan; Fajar Khaify Rizky (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2025)
Waste management is a strategic issue in preserving the environment, especially amid increasing waste volumes due to urbanisation and changes in people's lifestyles. The main problem that arises is the low level of public awareness of the law in sorting, processing and disposing of waste in accordance with applicable regulations. This independent community service activity by lecturers at Puri Zahara 2, Simpang Selayang Village, Medan Tuntungan Subdistrict, aims to increase public understanding of the importance of waste management in accordance with environmental law principles, particularly those stipulated in Law No. 18 of 2008 concerning Waste Management and its derivative regulations. The methods used were legal counseling, training in 3R (Reduce, Reuse, Recycle) waste management, and assistance in forming environmental law awareness groups. The results of the activity showed an increase in community knowledge and active participation in implementing environmentally friendly and legally-minded waste management practices, through the establishment of a Waste Bank in the Puri Zahara II Complex, Simpang Selayang Village, Medan Tuntungan District. Thus, this community service not only had an impact on reducing waste volume, but also built a legal culture that supports environmental sustainability.